Transição em modelos de negócio a partir de capacidades digitais: o desafio da tecnologia 5g no setor de games - I Sen Chen, Victor Alberto (2022)
From the perspective of Dynamic Capabilities, this dissertation seeks to portray how digital capabilities contribute to the transition of business models. The research is structured from the constructs of Innovation in Business models and Digital Capabilities. This study was developed in four companies in the games sector, impacted by the digital transformation with the entry of 5G technology. It is intended to understand how companies adapt their business models to respond to digital transformation, and the transition of business models in the sector occurs in response to the impact of new technologies. The study is qualitative, through multiple case studies based on semi-structured interviews among businesspeople, triangulated with interviews with professionals from sectoral entities and reports issued by specialized companies. As a theoretical contribution, from the perspective of dynamic capabilities, this study advances the transition process of business models resulting from technological innovations in the economic environment that trigger Schumpeterian creative destruction. The managerial implications bring insights to managers of creative economy sectors on how competitors react to digital transformation by transitioning their business models to streaming platforms.